PENGARUH FASILITAS TERHADAP KEPUASAN TAMU DI ARTOTEL GELORA SENAYAN JAKARTA - Zahri, Raihan Rizki; Aprilia, Lu’luwatin Rosdiana; Anggraeni, Rr. Christiana Mayang (LPPM Politeknik Pajajaran ICB Bandung, 2024)
This study aims to analyze the effect of facilities on guest satisfaction at Artotel Gelora Senayan Jakarta. Using a quantitative approach with an associative method, data were collected through a Likert-scale questionnaire and analyzed using simple linear regression. The sample consisted of 97 respondents from a population of 3,000 hotel guests (March–May 2025), determined using the Slovin formula with a 10% margin of error. The results showed that guests had a positive perception of the hotel’s facilities, including room comfort, Wi-Fi access, cleanliness, and other supporting amenities, and overall guest satisfaction was high. The regression analysis revealed a positive and significant relationship between facilities and guest satisfaction, with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.336, indicating that 33.6% of guest satisfaction is explained by the quality of the facilities. Therefore, well-managed facilities significantly contribute to increasing guest satisfaction, and hotel management is advised to continually improve the quality and completeness of its facilities.